A LGPD e as decisões resultantes do tratamento automatizado de dados pessoais. - Souza, Aurora de Barros (2023)
Data protection has been a subject debated by several new national and international legislations. The objective is to provide more security in cyberspace regarding the capture and processing of personal data. In Brazil, the Federal Constitution, the Consumer Defense Code, and the Civil Rights Framework for the Internet legislate on data protection, but it is the General Data Protection Law (GDPL) that specifically aims to protect the fundamental rights of freedom and privacy and the free development of the personality of the natural person. However, the GDPL was amended in its original text to allow for the processing of data in an automated way, without human intervention, including for the purpose of deciding on the profiles of the holders. Hence the concern about the effectiveness of data protection since the error rates by artificial intelligence algorithms are alarming and result in an increase in social inequality and discrimination. In this context, Brazil's position regarding data protection in a less judicious way, in favor of business models of financial institutions and startups, seems to connect with the systemic perception of the existence of the most beneficial regulatory environment for certain sectors, as well as the continuity of capitalism through digital and data colonialism, resulting in the need for new solutions for the effectiveness of data protection and the safeguarding of individual rights. In this wake, we proposed: 1) the adoption of digital civil education; 2) more rigorous application of data governance by public and private institutions, including addressing the UN's sustainable development goals; and 3) the structuring of legislation that acts in greater depth at the heart of the matter, regulating aspects related to algorithms and artificial intelligence, in order to make data processing more transparent and to enable both accountability and control by society civil law, as it has already been proposed by the European Union, the United States and in a still incipient form in Brazil in a Bill pending in the Federal Senate.